Dialektisk atferdsterapi for barn: En pilotstudie av ferdighetstreningsgrupper for foreldre - Marit Coldevin; Maia Daasvand Skyberg; Solveig M. Kirchhofer; Per Martin Løken; Synne Jenssen; Jan Stubberud (Tidsskrift for Norsk Psykologforening)
Dialectical behaviour therapy for children with severe emotional dysregulation: A pilot study of skill training groups for parentsBackground and purpose: The overall aim of the present pilot study was to examine how parents report treatment outcomes after participating in skill training groups in dialectical behaviour therapy for children (DBT-C). DBT-C was developed to meet the therapeutical needs of children with severe emotional dysregulation. To our knowledge, this is the first study in the world to explore treatment outcomes of skill training groups for parents in DBT-C. Methods and results: The sample in this within-subjects study consisted of parents of 23 children from an outpatient sample aged between eight and 13 years (Mdn = 11, 74 % boys). The outcome measures were the Eyberg Child Behaviour Inventory (ECBI), comparing scores pre- and post-intervention, and an evaluation of the perceived feasibility and acceptance of the intervention. Findings indicated a reduction in the frequency of disruptive behaviours (ECBI Intensity) (t(21) = 5.127, p < .001) and in the extent to which the parent finds the child’s behaviour troublesome (ECBI Problem) (t(19) = 2.714, p = .014) following intervention. Conclusion: With reservations for the small sample size and the lack of a control group, the present pilot study shows preliminary evidence that DBT-C skill training groups for parents reduce behavioural problems in children with emotional dysregulation. The study contributes to the scant research conducted to date on the promising effects of DBT-C and paves the way for further research of the treatment method. Keywords: DBT-C, DMDD, skill training groups, parent intervention, disruptive behaviour